Increased aortic pulse wave velocity in obese children - Çelik, Ataç; Özçetin, Mustafa; Yerli, Yasemin; Damar, İbrahim Halil; Kadı, Hasan; Koç, Fatih; Ceyhan, Köksal (Turkish Society of Cardiology, 2011)
Obesity may start in childhood and obese children are more likely to grow up to be obese adults. Atherosclerosis is one of the most important complications of obesity. Pulse wave velocity (PWV), a noninvasive measure of arterial stiffness, is accepted to be an indicator of subclinical atherosclerosis. The aim of the study was to determine PWV in obese children.The study included 30 obese (12 boys, 18 girls; mean age 13 ± 2 years) and 30 lean children (13 boys, 17 girls; mean age 12.5 ± 1.7 years). Weight and height were measured and obesity was defined as body mass index (BMI) of greater than the 95th percentile for age. All the subjects underwent echocardiographic evaluation and blood samples were obtained. Pulse-wave velocity was calculated using the following equation: PWV (m/sec) = height-based aortic length (cm)/(100xtransit time [sec]). The latter was measured as the difference in the time of onset of two flows at the diaphragm and the aortic valve.Obese subjects had significantly higher blood pressure levels compared to the control group (p<0.001). The two groups were similar with respect to fasting glucose, hemoglobin, serum creatinine, and lipid levels. Among echocardiographic parameters, left ventricular end-diastolic dimension, interventricular septum thickness, posterior wall thickness, left ventricular mass index, left atrium dimension, and aortic root dimension were significantly increased in obese subjects compared to controls (p<0.01). Obese children had significantly higher PWV values than the controls (4.0 ± 0.8 vs. 3.3 ± 0.7 m/sec, p<0.001). A positive significant correlation was found between PWV and BMI (r=0.391, p=0.002).Our findings show that aortic PWV is increased in obese children, suggesting that obesity may cause subclinical atherosclerosis even at early ages.
Keywords: Echocardiography, Doppler, Pulsed; Male; Adolescent; Cholesterol, HDL; Kalp ve Kalp Damar Sistemi; Cholesterol, LDL; Coronary Artery Disease; Body Mass Index; Cholesterol; Case-Control Studies; Pulsatile Flow; Humans; Female; Obesity; Child; Triglycerides; 2. Zero hunger; 3. Good health